ECONOMIC PERFORMANCE OF MOTOR GRADERS IN SUGARCANE (Saccharum spp.) PROCESSING PLANTS - Santos, Neisvaldo Barbosa Dos (ENERGIA NA AGRICULTURA, 2017)
Brazil is the world’s largest producer of sugarcane for mills. They use tractors with various agricultural of equipment in the mechanized operations of periodic soil preparation, planting, cropping and harvesting. Therefore, several studies have proven the economic importance of the cost generated by these machines. However, few studies highlight the performance of a motor grader, which has both functional and economic importance, due to its wide use in the agricultural activities in the mill. The objective of this study was evaluated of the systemic mode, the influence of economic performance variables in the cost and in time useful lifespan of a motor grader in an agricultural operation. In this study, machines with nominal power of 116 kW (158 cv) and 159 kw (216 cv) were utilized. For this study, a computational model called “TerraPlanCana” was developed in electronic spreadsheet and programming language. The results showed that the increase in the useful life in years reduces the fixed annual cost of the machines and when the hours of useful life increase, the hourly cost decreases. The increase of the useful life in year or hour raises the total cost, reducing the gains of the mill. KEYWORDS: Cost, Agricultural mechanization, Computer model, Income, Fleet renewal. DESEMPENHO ECONÔMICO DE MOTONIVELADORAS EM USINA DE CANA-DE-AÇÚCAR (Saccharum spp.) Resumo: O Brasil é o maior produtor mundial de cana-de-açúcar para as usinas. Estas utilizam tratores com diversos equipamentos agrícolas, nas operações mecanizadas de preparo periódico do solo, plantio, tratos culturais e colheita. Devido a isso, diversos estudos tem comprovado a importância econômica do custo gerado por estas máquinas. Entretanto, existe a motoniveladora, que tem importância funcional e econômica, devido sua ampla utilização nas atividades agrícolas das usinas e poucos estudos destacam seu desempenho. O objetivo do trabalho foi avaliar de modo sistêmico, a influência das variáveis de desempenho econômico no custo e no tempo de vida útil da motoniveladora em operação agrícola. No trabalho foram consideradas máquinas com potência nominal de 116 Kw (158 cv) e de 159 Kw (216 cv). Para o trabalho foi desenvolvido um modelo computacional, denominado “TerraPlanCana”, em planilha eletrônica e em linguagem de programação. Os resultados evidenciaram que o aumento da vida útil em anos reduz o custo fixo anual das máquinas e quando crescem as horas de vida útil o custo horário diminui. O crescimento da vida útil em ano ou em hora eleva o custo total, diminuindo os ganhos da usina. PALAVRAS-CHAVE: Custo, Mecanização Agrícola, Modelo computacional, Renda, Renovação de frota.